Effect of Harvesting of Fruits at Different Maturity Stage on the Production of Cucumber (Cucumis sativus L) Under Plastic House Condition - Dayamand Pokharel; Abichal Poudel; Karuna Kafle (International Journal for Research in Applied Sciences and Biotechnology, 2021)
The experiment was carried out from 16th December 2016 to May 10, 2017, in the horticulture farm of Nepal Polytechnic Institute Bharatpur-11. Cucumbers were planted under plastic house conditions (23.90 ± 3.55 ̊C temp. and 59.15 ± 10.33% RH). Parthenocarpic cucumber variety Poyraz F1 was selected for the research. Fruits are harvested at four different maturity stages (Maturity stage 1, 2, 3, and 4) were treatments i.e. M1 – Immature stage 1 (harvesting of fruits after 2 weeks of fruit set), M2 – Immature stage 2 (harvesting of fruit after 3 weeks of fruit set), M3 – Mature stage (harvesting fruits after 4 weeks of fruit set) and M4 – Over-mature stage (harvesting fruits after 5 weeks of fruit set). Each treatment was replicated 5 times with 5 plants in each experimental unit and these experimental units were arranged in a completely randomized design. There was a significant difference among the selected treatments in the number of flowers per plant at 30, 45 & 60 DAT, the number of internodes per plant at 45 & 60 DAT, numbers of fruits per plant at 30, 45 & 60 DAT and number of harvest per plant. The total yield per plant was observed as not significant. Highest no. of flowers (6.88, 15.52 and 5.83 at 30, 45, and 60 DAT), nodes (5.44, 6.76, 10.53 and 15.53 at 15, 30, 45 and 60 DAT) and fruits (1.4, 5.6, 15 and 25.2 at 15, 30, 45 and 60 DAT) per plant were recorded in the plant in which fruits were harvested at immature stage 1 (harvesting fruits at 2 weeks of fruit set) whereas their values were minimum in the plants in which fruits were harvested at over-mature stage (harvesting fruits at 5 weeks of fruit set). A maximum number of harvests (6.40) were recorded in the plants in which fruits were harvested at an earlier maturity stage. Yield per plant did not vary significantly. Hence, it would be better to harvest cucumbers at an immature stage as the fruit harvested at an earlier stage of maturity had more number of harvests and the producer could enjoy the different market prices and higher prices by supplying tender fruits.